2011
DOI: 10.1007/s00442-011-1905-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic size determines population-level effects of fungal parasites on Daphnia hosts

Abstract: Parasites frequently reduce the fecundity, growth, and survival of individual hosts. How often do these virulent effects reduce the density of host populations? Spectacular examples show that recently invaded parasites can severely impact host populations--but what about parasites persisting long-term in host populations? We have addressed this issue using a zooplankton host (Daphnia dentifera) that becomes infected with a fungal microparasite (Metschnikowia bicuspidata). We combined observations of epidemics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 53 publications
4
52
0
Order By: Relevance
“…Smith (1977) previously showed that the spatial distribution of two sympatric water boatmen was determined by the presence of water mites, which exclude one of them at lower salinity. In many host-parasite systems, values of prevalence exceeding 10 %, as in our study for T. v. verticalis, are enough to exert a negative influence on host density (Hall et al 2011). Moreover, total prevalence and intensity of mites recorded in our study were probably underestimates.…”
Section: Ecological Impact Of Mite Infection and Consequences For T mentioning
confidence: 93%
“…Smith (1977) previously showed that the spatial distribution of two sympatric water boatmen was determined by the presence of water mites, which exclude one of them at lower salinity. In many host-parasite systems, values of prevalence exceeding 10 %, as in our study for T. v. verticalis, are enough to exert a negative influence on host density (Hall et al 2011). Moreover, total prevalence and intensity of mites recorded in our study were probably underestimates.…”
Section: Ecological Impact Of Mite Infection and Consequences For T mentioning
confidence: 93%
“…Contamination reduced the total size of epidemics in Daphnia populations by 50 per cent relative to epidemics occurring in uncontaminated conditions. This reduction in epidemic size matters because larger epidemics typically reduce densities of Daphnia more severely [35]. Indeed, Daphnia populations experienced a smaller parasite-induced decline in densities in copper contaminated tanks with smaller epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…Virulent parasites can harm host populations (Frick et al 2010, Vredenberg et al 2010, Hall et al 2011, alter competitive interactions (e.g., Tompkins et al 2003), and exert strong selective pressure on hosts . The emergence and resurgence of infectious diseases among wildlife populations also poses a major challenge for species conservation (Frick et al 2010, Vredenberg et al 2010, Fisher et al 2012.…”
Section: Introductionmentioning
confidence: 99%